Indonesia’s Environmental Crimes: A Critical Perspective of the ‘State’ as the ‘Victim’ - Rismanto, Pipit; Muhammad Krisna Bayunarendro (Sekolah Tinggi Ilmu Kepolisian, 2024)
In the midst of various environmental crimes that are being increasingly profiled around the world, the perspective of the ‘state’ is often overlooked as the entity of the ‘victim’. In fact, in addition to individuals, communities, and the environment the state is often harmed from various environmental crimes. Through a qualitative approach with the methods of Qualitative Content Analysis (QCA), an Extended Literature Review (ELR), and Critical Discourse Analysis (CDA), this paper finds the direct and indirect impacts of the outbreak of environmental crimes in Indonesia from the perspective of the ‘state’. This papers also examines the many paradoxes that can be created when the law is used by the state as the solution. In addition, this paper explores various SGC perspectives that emphasise considering the socio-economic and historical-cultural contexts of countries in the Global South. Finally, this paper recommends a transformative justice approach that emphasises reforms and improvements to governance that are more inclusive and sustainable, primarily to address environmental crimes in Indonesia that also focus on restoring environmental damage. This paper also emphasises the importance of strengthening regulations and education related to sustainable environmental education for the community. With a focus on positioning the state as a victim, this research is expected to fill a gap in the literature and be useful in the practical realm.